Ketone therapy for heart failure: current evidence for clinical use. Issue 4 (11th March 2021) - Takahara, Shingo; Soni, Shubham; Maayah, Zaid H; Ferdaoussi, Mourad; Dyck, Jason R B
Abstract: During conditions that result in depleted circulating glucose levels, ketone bodies synthesized in the liver are necessary fuel substrates for the brain. In other organs, such as the heart, the reliance on ketones for generating energy in the absence of glucose is less important as the heart can utilize alternative fuel sources, such as fatty acids. However, during pathophysiological conditions, such as heart failure, cardiac defects in metabolic processes that normally allow for sufficient energy production from fatty acids and carbohydrates contribute to a decline in contractile function. As such, it has been proposed that the failing heart relies more on ketone bodies as an energy source than previously appreciated. Furthermore, it has been shown that ketone bodies function as signaling molecules that can suppress systemic and cardiac inflammation. Thus, it is possible that intentionally elevating circulating ketones may be beneficial as an adjunct treatment for heart failure. Although many approaches can be used for 'ketone therapy', each of these has their own advantages and disadvantages in the treatment of heart failure. Thus, we summarize current preclinical and clinical studies involving various types of ketone therapy in cardiac disease and discuss the advantages and disadvantages of each modality as possible treatments for heart failure. Graphical Abstract: